Water use strategy affects avoidance of ozone stress by stomatal closure in Mediterranean trees—A modelling analysis. (10th January 2020) - Hoshika, Yasutomo; Fares, Silvano; Pellegrini, Elisa; Conte, Adriano; Paoletti, Elena
Abstract: Both ozone (O3 ) and drought can limit carbon fixation by forest trees. To cope with drought stress, plants have isohydric or anisohydric water use strategies. Ozone enters plant tissues through stomata. Therefore, stomatal closure can be interpreted as avoidance to O3 stress. Here, we applied an optimization model of stomata involving water, CO2, and O3 flux to test whether isohydric and anisohydric strategies may affect avoidance of O3 stress by stomatal closure in four Mediterranean tree species during drought. The data suggest that stomatal closure represents a response to avoid damage to the photosynthetic mechanisms under elevated O3 depending on plant water use strategy. Under high‐O3 and well‐watered conditions, isohydric species limited O3 fluxes by stomatal closure, whereas anisohydric species activated a tolerance response and did not actively close stomata. Under both O3 and drought stress, however, anisohydric species enhanced the capacity of avoidance by closing stomata to cope with the severe oxidative stress. In the late growing season, regardless of the water use strategy, the efficiency of O3 stress avoidance decreased with leaf ageing. As a result, carbon assimilation rate was decreased by O3 while stomata did not close enough to limit transpirational water losses. Abstract : In carbon‐starved red‐fleshed kiwifruit both carbohydrate and anthocyanin concentrations were greatly reduced. Our model suggests anthocyanin biosynthesis was actively repressed by MYB27 via trehalose 6‐phosphate signalling to conserve carbon.